Gendered Images of Music and Musicians: Report from the Congress of the ”Music and Gender” Study Group of The International Council for Traditional Music - Sorin, Ragnhild (Svensk tidskrift för musikforskning / Swedish Journal of Music Research, 1999)
Report from the Congress of the ”Music and Gender” Study Group of The International Council for Traditional Music January 20-24, 1999 Congress organizer: Professor Pirkko Moisala. Åbo Akademi, Finland Congress secretary: Paulina Ahokas